Guest editorial – Special issue: Environmental, social, governance, and taxation - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2024)
This special issue of the eJournal of Tax Research comprises five articles that are a selection of papers that were originally presented at the SMU–Edinburgh Environmental, Social, Governance and Taxation Conference hosted by the Yong Pung How School of Law, Singapore Management University in April 2024.